The Life of Isaac Ingalls Stevens, Volume 2 (of 2) - Stevens, Hazard, 1842-1918 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Life of Isaac Ingalls Stevens, Volume 2 (of 2)" by Hazard Stevens is a historical account written in the late 19th century. This biography explores the life and political career of Isaac Ingalls Stevens, focusing particularly on his role as a governor and his negotiations with Native American tribes in the Pacific Northwest. The work delves into Stevens' efforts to establish treaties and maintain peace amid rising tensions between white settlers and Indigenous communities. The opening of the book details the Chehalis Council, where Governor Stevens convenes a meeting with several Indian tribes to negotiate treaties. The narrative paints a vivid picture of the council's atmosphere, showcasing the interactions between Stevens, his team, and the Native American leaders. Key events include the colorful arrival of tribes, the adaptations made by both parties during the negotiations, and the challenges faced due to misunderstandings and resistance from some tribal leaders. Through these initial interactions, the text sets the stage for the complex dynamics at play in Stevens' quest for cooperation and peace in a time of significant cultural change and conflict. (This is an automatically generated summary.)
Release date is 2013-08-31
E-text prepared by KD Weeks, Jana Srna, Bryan Ness, Jennie Gottschalk, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Google Books Library Project (http://books.google.com)
Keywords: United States -- History -- Civil War, 1861-1865 -- Campaigns; Mexican War, 1846-1848 -- Personal narratives; Northwest, Pacific -- History; Stevens, Isaac Ingalls, 1818-1862; Pacific Coast Indians, Wars with, 1847-1865